Fatores relacionados ao desempenho da Atenção Primária à Saúde nas ações de controle da hanseníase - Nayara Figueiredo Vieira (2019)
In view of the heterogeneity that characterizes the integration of leprosy control actions in primary health care, it is fundamental to understand the factors that contribute to the quality of services, considering the disease as a public health problem, epidemiological importance in the territory and strategic area of action of the primary care services. This study aimed to evaluate the degree of orientation of primary health care in the actions of control and elimination of leprosy in Belo Horizonte and to identify factors that influence the performance of services. Cross - sectional study, carried out with 70 Family Health Teams of Belo Horizonte, from July to September / 2014. 408 professionals were interviewed, of which 189 were managers, 65 doctors, 79 nurses and 75 Community Health Agents. An evaluation tool was used to measure the orientation of primary care in the implementation of leprosy control actions. (access, door of entry, integrality of services available, integrality of services provided, coordination, professional orientation, family orientation and community orientation). Subsequently, leprosy monitoring indicators were calculated using the historical series average from 2012 to 2016, based on the Notification of Injury Information System. The Spearman's correlation and the multiple-bootstrap linear regression model were used to analyze the association of the degree of primary care orientation in the leprosy actions with explanatory factors (significance level p <0.05). Most of the participants have been working in primary care for more than 10 years, 62% reported having leprosy control actions in the territory, and, for the most part, they did not follow cases of the disease and 48.8% were not trained. Regarding the epidemiological behavior, there was heterogeneity in the health districts of Belo Horizonte, with variations in health indicators. In the evaluation of the degree of orientation of primary care in the leprosy actions, it was observed a poor orientation from the perspective of the doctors and nurses, however, from the perspective of the health districts strong orientation. There was correlation between general score and percentage of cases treated in primary care and family health care coverage. In the derived score, there was correlation with the percentage of cases treated in primary care, and, essentially, with the proportion and rate of diagnosed cases, grade 2 of physical disability. Strong orientation was observed in the essential and general score, and association with leprosy training. In the derived score, poor orientation and association with the training for physicians and community health agents. The manager presented a conservative evaluation when compared to the other categories of participants, and the most significant differences were observed in the evaluation of the derived score. The quality of leprosy control actions carried out by primary care professionals produces impacts on health indicators, and it is necessary to elaborate strategies consistent with the reality of the territory. The professional experience of the family health team in assisting leprosy is determinant for the service to be the provider of control actions oriented according to the essential attributes and derived from primary care. Brazil has made progress in reducing incidence, but should increase the effectiveness of health surveillance as a means of strengthening early detection and training of professionals.